Fluid resuscitation in burns: an update - Chan, J; Ghosh, S (2009)
Fluid resuscitation has been a mainstay in the treatment of major burns for over 50 years. Fluids must be commenced as soon as possible prior to transfer to a specialist unit in order to minimise burn wound conversion and reduce the incidences of burn shock, post-burn renal failure, life-threatening electrolyte disturbances and mortality Due to the lack of robust evidence, uncertainty exists regarding the type of fluid, the rate of fluid administration and method of monitoring fluid resuscitation in these patients. The advances in our understanding of burn pathology and technology may have rendered fluid resuscitation formulae, such as the Parkland, obsolete. This review aims to provide an up-to-date summary on the controversies and advances in burns fluid resuscitation to aid the emergency practitioner to make informed decisions.